Tailing dumps of the tyrnyauz tungsten-molybdenum mining and processing complex: Current state and outlooks - NS Bortnikov; AG Gurbanov; Alexander Y Dokuchaev (Global Journal of Ecology - Peertechz Publications, 2020)
The Tyrnyauz W-Mo deposit was developed by opencast and underground mines until 2003. The assets of the Tyrnyauz Tungsten-Molybdenum Mining and Processing Complex (TTMC) include two tailing dumps: Tailing 2 (housed on the left-hand side of the Baksan River valley, 2 km south of the settlement of Bylym) and Supertailing 2 (a superdump housed in the valley of the Gizhgit River, a left-hand tributary of the Baksan River). The height of the rock-filling dam of Supertailing 1 reaches 160 m. A pond on its top protects the ecosystems from the wind erosion of the dumped industrial wastes. The protecting pond is equipped with a tunnel drainage system, which is used to discharge excess water to the Baksan River, to a certain technological water level in the pond. Shallow-focus earthquakes (with M = 5-7) and/or debris and mud flows are able to destroy the dam, and this will result in the transfer of toxic compounds to the Baksan River and water-bearing Quaternary alluvial rocks in the foredeep, where the river flows into the plain. The following soil contamination sources were identified: (1) Winds continuously blowing along the Baksan valley erode fines where the recultivation layer of Tailing 2 is disturbed and in the beach parts of Supertailing 1; the extent of this contamination varies from hundreds of meters to a few kilometers; (2) Massive blasting operations at the opencast mines before 2003 resulted in atmospheric emissions of dust clouds with ore minerals; this pollutions extends for dozens of kilometers (along the valleys of the Baksan River and its tributaries). The most ecologically hazardous emissions are those of quartz dust and dust with heavy-metal minerals, including sulfides. A method for utilizing TTMC wastes was engineered and patented. The results provide a basis for designing measures aimed at decreasing the adverse load on the ecosystems in the Elbrus area, which is highly attractive to tourists.